2011
DOI: 10.1007/s11434-011-4561-5
|View full text |Cite
|
Sign up to set email alerts
|

Etching mechanism of barium strontium titanate (BST) thin films in CHF3/Ar plasma

Abstract: Reactive ion etching was used to etch barium strontium titanate thin films in a CHF 3 /Ar plasma. BST surfaces before and after etching were analyzed by X-ray photoelectron spectroscopy to investigate the reaction ion etching mechanism, and chemical reactions had occurred between the F plasma and the Ba, Sr and Ti metal species. Fluorides of these metals were formed and remained on the surface during the etching process. Ti was almost completely removed because the TiF 4 by-product is volatile. Minor quantitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Dry-etching processes as a micro-patterning technology are very important in integrating the BZN thin films into a Si-based circuitry. Many studies on dry-etching processes for various kinds of specimens have been reported [9][10][11][12][13][14][15][16], where various of etching parameters having effects on the surface and structure of films were involved. However, only a few studies on BZN thin films have been published [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Dry-etching processes as a micro-patterning technology are very important in integrating the BZN thin films into a Si-based circuitry. Many studies on dry-etching processes for various kinds of specimens have been reported [9][10][11][12][13][14][15][16], where various of etching parameters having effects on the surface and structure of films were involved. However, only a few studies on BZN thin films have been published [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…BTO patterns have been defined using sacrificial SiO 2 lift-off procedures or Cl etching . However, the build-up of Ti-containing etch products on the surface , and decreasing nanofeature dimensions make monolithic integration of patterned perovskites difficult using existing techniques. A potential solution to the challenges in defining crystalline BTO patterns is bottom–up area-selective (AS) patterning.…”
Section: Introductionmentioning
confidence: 99%